The Stabilizing Role of Forward Guidance: A Macro Experiment - Steffen Ahrens; Joep Lustenhouwer; Michele Tettamanzi (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We study if central banks can manage market expectations by means of forward guidance in a New Keynesian learning-to-forecast experiment. Subjects observe public inflation projections by the central bank along with the historic development of the economy and subsequently submit their own inflation forecasts. We find that the central bank can significantly manage market expectations through forward guidance and that this management strongly supports monetary policy in stabilizing the economy.
Keywords: C92; E32; E37; E58; 330